Modeling bromate formation during ozonation - Jarvis, Peter; Parsons, Simon A.; Smith, Rosie (Taylor & Francis, 2007)
Bromate formation has been identified as a significant barrier in the application of ozone during water treatment for water sources that contain high levels of bromide. Bromate has been identified as a possible human carcinogen and bromate levels in drinking water are strictly controlled at 10 mu g/L in most developed countries. Various models have been proposed to model bromate formation during ozonation based on raw water quality, ozone dose and contact time. Two main approaches for modeling have been used: an empirical regression modeling methodology and kinetic-based methodology. Currently, the benefit of the bromate models lies in their ability to show how process parameters may impact on the amount bromate formed.
Keywords: ozone bromate kinetics modeling multiple linear regression artificial neural networks drinking-water product formation dissolved ozone by-products disinfection chlorine bromide minimization generation oxidation